Polish adaptation policy to climate change vs. EU countries' adaptation policies - Dorota Michalak; Paulina Szyja (Comparative Economic Research. Central and Eastern Europe, 2023)
The purpose of this study is to compare the advancement of Poland's adaptation policy with the policy of other EU countries. Benchmarking was used, and the research was preceded by comparing the degree of climate change impact on the economies of individual EU countries. The study used 12 comparative quantities, forecast to 2100 for 27 countries. The added value of the analysis is the diagnosis that indicates whether the advancement of the adaptation policy of individual countries is appropriate for the projected climate change, together with the indication of the level of the adaptation policy in Poland compared to other member states. It was determined that, compared to Western countries, Poland has the lowest projected impact of climate change, as represented by selected indicators in the study, but it also has the lowest degree of adaptation policies. However, comparing Poland with the other countries that joined the EU in 2004 shows the opposite trend. The survey is a starting point for further analysis of adaptation in its broadest sense, at national, EU, and global levels. It indicates that despite the high rate of increase in the negative consequences of climate change, the implementation of adaptation policies is still insufficient and often at an early stage of planning.
Keywords: 330; climate change; adaptation; adaptation policies